Propagation of Diffusion-Weighted MRI Abnormalities in the Preclinical Stage of Sporadic Creutzfeldt-Jakob Disease. (18th October 2022) - Yasuda, Manato; Sugiyama, Atsuhiko; Hokkoku, Hideharu; Suichi, Tomoki; Ito, Kimiko; Satoh, Katsuya; Kitamoto, Tetsuyuki; Kuwabara, Satoshi
Abstract : Objectives: Currently, no established biomarkers exist for presymptomatic sporadic Creutzfeldt-Jakob disease (sCJD). The purpose of this study was to raise awareness about sCJD cases showing abnormalities on brain MRI diffusion-weighted imaging (DWI) before symptom onset and demonstrate temporal changes in DWI abnormalities during the preclinical period. Methods: We described the clinical presentation including the results of MRI—performed multiple times in the preclinical period—and the diagnostic workup of a middle-aged man with sCJD. Results: MRI of the brain performed 27 months before symptom onset revealed an extremely localized lesion on DWI in the right occipital cortex. Follow-up MRI scans showed propagation of DWI abnormalities along the cortices without the appearance of neurologic symptoms/signs. After symptom onset, the patient's neuropsychiatric condition rapidly deteriorated. Elevated total tau protein levels and positive 14-3-3 protein were observed in the CSF, and periodic synchronous discharges using electroencephalography resulted in the diagnosis of sCJD. Discussion: CJD should be considered in differential diagnoses when localized DWI signal abnormalities propagate along the cortices over time, even in the absence of typical CJD symptoms. DWI signal abnormalities on brain MRI scans may be highly sensitive diagnostic markers for CJD, even in the preclinical stage.